Transcriptomal changes and functional annotation of the developing non-human primate choroid plexus - Ek, C. Joakim; Nathanielsz, Peter; Li, Cun; Mallard, Carina (Frontiers in Neuroscience, 2015)
The choroid plexuses are small organs that protrude into each brain ventricle producing cerebrospinal fluid that constantly bathes the brain. These organs differentiate early in development just after neural closure at a stage when the brain is little vascularized. In recent years the plexus has been shown to have a much more active role in brain development than previously appreciated thereby it can influence both neurogenesis and neural migration by secreting factors into the CSF. However, much of choroid plexus developmental function is still unclear. Most previous studies on this organ have been undertaken in rodents but translation into humans is not straightforward since they have a different timing of brain maturation processes. We have collected choroid plexus from three fetal gestational ages of a non-human primate, the baboon, which has much closer brain development to humans. The transcriptome of the plexuses was determined by next generation sequencing and Ingenuity Pathway Analysis software was used to annotate functions and enrichment of pathways of changes in the transcriptome. The number of unique transcripts decreased with development and the majority of differentially expressed transcripts were down-regulated through development suggesting a more complex and active plexus earlier in fetal development. The functional annotation indicated changes across widespread biological functions in plexus development. In particular we find age-dependent regulation of genes associated with annotation categories: Gene Expression, Development of Cardiovascular System, Nervous System Development and Molecular Transport. Our observations support the idea that the choroid plexus has roles in shaping brain development.